Urgensi Partisipasi Masyarakat Dalam Pembentukan Rancangan Undang-Undang Masyarkat Hukum Adat - Aditya Ardiansyah; Izzatusholekha (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
The community needs to participate in the formation of the Draft Law on Customary Law Communities. By looking at the various problems that occur regarding Community Participation in the Formation of Draft Laws, the prevalence of Draft Laws does not realize community participation in the formation process, especially the Draft Law on Customary Law Communities. This raises issues and questions regarding community participation in the formation of the Draft Law on Indigenous Peoples, whether it has been implemented or not. Arnstein stated that community participation is synonymous with community power (citizen participation is citizen power). This research aims to determine, describe and analyze Community Participation in the formation of the Draft Law on Customary Law Communities. This research uses qualitative methods, namely interviews, observation and documentation. The research and research results use Arnstein's theory, namely delegated power, that the Draft Law on Customary Law Communities is included in the Delegated Power stage (delegated power). Therefore, the urgency of community participation in the formation of the Draft Law on Customary Law Communities is very important.